2023
DOI: 10.3389/fcell.2023.1020965
|View full text |Cite
|
Sign up to set email alerts
|

Rapid direct conversion of bovine non-adipogenic fibroblasts into adipocyte-like cells by a small-molecule cocktail

Abstract: Introduction: The molecular regulation mechanism of fat deposition in bovine and its improvement on beef quality are important research directions in the livestock industry. The research of molecular mechanisms that govern the regulation and differentiation of adipocytes may conduct to understand the mechanism of obesity, lipid disorders, and fat deposition. In the recent decade, small-molecule compounds have been widely used in reprogramming and transdifferentiation fields, which can promote the induction eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…Fibroblasts have thus been the subject of attention in regeneration medicine because they were the first cell line used for differentiation into iPSC. Subsequent studies showed that fibroblasts can be differentiated directly into many types of cells, including myofibroblasts, osteogenic cells, chondrocytes, neurons, vascular endothelial cells, cardiac cells, 2 hepatocytes, 3 brown adipocytes, 4 , 5 and pancreatic β cells 6 (Figure 1 ). These findings led to the development of an approach using direct cellular reprogramming rather than iPSC‐based reprogramming, which is a time‐consuming and costly approach.…”
Section: Introductionmentioning
confidence: 99%
“…Fibroblasts have thus been the subject of attention in regeneration medicine because they were the first cell line used for differentiation into iPSC. Subsequent studies showed that fibroblasts can be differentiated directly into many types of cells, including myofibroblasts, osteogenic cells, chondrocytes, neurons, vascular endothelial cells, cardiac cells, 2 hepatocytes, 3 brown adipocytes, 4 , 5 and pancreatic β cells 6 (Figure 1 ). These findings led to the development of an approach using direct cellular reprogramming rather than iPSC‐based reprogramming, which is a time‐consuming and costly approach.…”
Section: Introductionmentioning
confidence: 99%